Board characteristics and environmental, social, governance (ESG) disclosure: Evidence from China - ZEQUN, ZHAO (2022)
Due to far-reaching problems such as ecological diversity and climate change, the ESG movements have gained steam in the past few decades. Investors and executives have been increasingly placing greater emphasis on long-term concerns and non-financial reporting. However, the determinants of ESG information disclosure are still unclear in some developing countries, where ESG disclosure is not mandatory. Therefore, this paper contributes to the ESG literature by examining the impact of board characteristics on ESG disclosure in Chinese context. This paper found that the existence of female directors and directors with foreign experience could significantly promote ESG reporting, CEO duality also has a positive impact. However, this paper found a negative relationship between the proportion of independent directors and ESG disclosure.